Effectiveness of herbicides on Lysimachia vulgaris: a 17-year case study. (14th December 2020) - De Luccia, Marisa R.; Peterson, Ben; Bradshaw, Michael J.; Tobin, Patrick C.
Abstract: Garden loosestrife ( Lysimachia vulgaris L.), is an invasive wetland plant that is subject to management in King County, WA, USA. Large-scale management efforts are generally conducted using herbicides. In this case study, we analyzed 17 yr of monitoring and treatment data in four riparian areas in King County to estimate the rate of spread of L. vulgaris and the efficacy of herbicidal treatments against L. vulgaris populations. In each area, herbicide treatments were applied annually. In three of the areas, the area infested with L. vulgaris did not change over time, while in the fourth area populations of L. vulgaris were spreading at a rate of 0.79 m 2 yr −1 . There were a greater number of sampled locations infested with L. vulgaris over the 17-yr period, and because populations were either not spreading or spreading slowly, it is possible that populations were becoming more fragmented. There was no relationship between the percentage of the infested area treated with herbicides and the area infested in the following year. However, there was a negative relationship between the area treated and the percent change in the invaded area; specifically, in years when <80% of the infested area was treated, there was an increase in the percent change of the invaded area between the year of treatment and the following year. The results of this study suggest that at the current level of management effort, the spatial extent of L. vulgaris did not retract over the 17-yr study period.